Development and Effectiveness of a Canva-Based Problem-Based Learning E-Module Using the 4D Model to Improve Students’ Understanding of Molecular Shapes - Ester Ndruru; Nora Susanti; Jhonatan Ariski Lumbantobing (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and evaluate the effectiveness of a Canva-based e-module using the Problem-Based Learning (PBL) approach to improve students’ understanding of molecular shapes. The research employed a Research and Development (R&D) method using the 4D model (define, design, develop, disseminate). The effectiveness test applied a one-group pretest–posttest design involving 35 tenth-grade students at SMA Negeri 2 Medan selected through purposive sampling. The research instrument consisted of a multiple-choice test that was validated and tested for reliability (KR-20 = 0.811). Data analysis techniques included normality test, paired sample t-test, and N-gain analysis. The validation results showed that the e-module was highly feasible, with scores of 90.56% from media experts and 89.38% from material experts. The paired t-test results indicated a significant difference between pretest and posttest scores (p < 0.05), supported by an N-gain value of 0.76 (high category). These findings indicate that the Canva-based PBL e-module is both feasible and statistically effective in improving students’ understanding of molecular shapes.